(untitled) (Indian Journal of Child Health, 2019)
Background: Approximately 3–4% of neonates with meconium-stained amniotic fluid (MSAF) develop meconium aspiration syndrome (MAS), of which nearly 30–50% need continuous positive airway pressure (CPAP) or mechanical ventilation (MV). Objective: The objective of the study was to evaluate the usefulness of bubble CPAP as a respiratory support in neonates admitted with MAS and to enumerate factors affecting the CPAP failure. Materials and Methods: A prospective study was conducted, involving all the neonates born with a history of MSAF with respiratory distress within 6 h of life (Downe’s score 4–7), SpO2 <90% with chest X-ray suggestive of MAS. Bubble CPAP was started with pressure and FiO2 adjusted to maintain a SpO2 between 89% and 95%, maximum pressure limit of 6 cm, and FiO2 of 100%, respectively. CPAP was removed when SpO2 was >90% with FiO2 requirement <25% and when respiratory distress was passive (Respiatory rate <60/min, no or mild retractions and no grunt). The primary outcome was measured in terms of improvement in Downe’s score and clinical condition of neonates. CPAP failure was defined as the need for MV, pulmonary leak syndrome, persistent pulmonary hypertension, and progression of Downe’s score. Results: Downe’s score at the start of CPAP was 6 which decreased to 4, 6 h post-CPAP. There was an improvement in FiO2, RR, and heart rate from 68%, 76/min, and 181/min to 84%, 48/min, and 123/min post-CPAP, respectively. The success rate of CPAP was 77% and failure rate was 23%. Conclusion: Early initiation of CPAP in MAS neonates decreases the need for MV and improves outcomes.